Genetic diversity of Fusarium fujikuori isolated from bakanae disease of rice on the basis of vegetative compatibility - Mohd Zainuddin, Nur Ain Izzati; Mohamed Sidique, Siti Nordahliawate; Salleh, Baharuddin (Universiti Putra Malaysia Press, 2008)
Fusarium fujikuroi which was originally studied in Japan is a pathogen of bakanae disease of rice. The disease was recorded in almost all countries where rice is grown commercially, including Malaysia and Indonesia. A total of 79 strains of F. fujikuroi were isolated from rice plants showing typical bakanae symptoms from major granary areas in Malaysia and Indonesia. They were identified using morphological characteristics for species delimitation. The objective of this study was to investigate genetic diversity of the F. fujikuroi strains by generating nitrate nonutilizing (nit) mutants, followed by phenotyping on diagnostic media, and pairing the mutants on minimal media (MM). About 96.2% of the strains were identified as heterokaryon self-compatible (HSC) based on their ability to form a stable heterokaryon while the remaining 3.8% of the strains were classified as heterokaryon selfincompatible (HSI) based on their inability to form a heterokaryon, even after repeated attempts. Those HSC strains that paired by producing robust growth were classified in the same vegetative compatibility group (VCG). The bakanae strains of F. fujikuroi were grouped into 26 VCGs; the largest group was VCG A01 which comprised of 23 strains. Out of 26 VCGs, 12 VCGs contained more than one strain member, and 14 VCGs were represented by a single strain and were not compatible with other strains. The ratio of VCGs to strains of F. fujikuroi in these samples was 0.29. The strains of F. fujikuroi that caused bakanae disease of rice in Malaysia and Indonesia are genetically diverse based on their multiple VCGs.